Hubungan Waktu Tunggu Penyediaan Rekam Medis Terhadap Kepuasan Pasien Di UPTD. Puskesmas Muara Wis - Maria Sartika; Mardahlia, Dewi; Nurhasanah, Nurhasanah (Jurnal Media Informatika, 2024)
Abstract− Waiting time is the time used by patients to get doctor's health services. The minimum service standard for a patient's medical record is less than 10 minutes. Based on a preliminary study conducted on medical record officers at UPTD. Muara Wis Health Center from 10 medical record documents found that 6 medical record documents were not in accordance with standards and 4 medical record documents were in accordance with standards. This study uses a quantitative method with a Cross-Sectional approach to analyze the relationship between waiting time for the provision of medical record documents and patient satisfaction at UPTD. Muara Wis Health Center, the sample consisted of 60 respondents who were selected using the Accedental Sampling technique, data collection instruments in the form of observations and questionnaires on the Likert scale, and the analysis was carried out through descriptive analysis and chi-square tests processed using computer application software. Based on the average results of the waiting time for the provision of medical record documents at UPTD. The Muara Wis Health Center takes 10 minutes and 40 seconds from 60 medical record documents. The calculation of the provision of medical records to patients begins when the patient registers until the medical record is available at the polyclinic. Suggestions for UPTD. Muara Wis Health Center in order to shorten the waiting time for officers to provide medical record files and re-evaluate their performance periodically.